(untitled) (PETITUM, 2020)
The research aims at examining the role of the State in the social and economic sustainability of natural resources around mining and the role of the community in enforcing environmental laws. This type of research uses normative legal research. The results of the study suggest that the responsibility of the State in restoring the mining environment must be carried out in the entire process starting from the stages of fulfilling permits, planning, implementing and controlling because the responsibility of business entities has not yet been regulated by the possibility of contaminating ex-mining areas after handover to the government. Post-mining environmental restoration activities only involve the authorities of the government and mining business actors without involving the community as an important element as well as parties directly related to the physical, economic and social environment of the mining environment. Penelitian bertujuan tentang meninjau peran Negara atas keberlanjutan sumber daya alam di sekitar pertambangan secara sosial dan ekonomi dan peran serta masyarakat dalam penegakan hukum lingkungannya. Jenis penelitian ini menggunakan penelitian hukum normatif. Hasil penelitian mengemukakan bahwa tanggungjawab Negara dalam pemulihan lingkungan pertambangan harus dilakukan pada seluruh proses mulai dari tahapan pemenuhan perizinan, perencanaan, pelaksanaan dan pengawasan karena belum diaturnya tanggungjawab oleh badan usaha terhadap kemungkinan pencemaran bekas lahan tambang setelah penyerahan kepada pemerintah. Kegiatan pemulihan lingkungan pada pascatambang hanya melibatkan kewenangan pemerintah dan pelaku usaha pertambangan tanpa melibatkan masyarakat sebagai unsur penting dan juga pihak yang terkait langsung dengan keberadaan lingkungan fisik, ekonomi maupun sosial lingkungan pertambangan.